ECOSTRESS-Based Analysis of Diurnal Urban Heat Island Intensity and Thermal Dynamics Across LCZ in Six Chinese Cities With Diverse Terrain and Elevation - Wang, Jiaqi; Cui, Xiaoyu; Zhao, Feng; Huang, Meiqi; Guo, Yuexia; Wang, Qirui; Shao, Bo; Tong, Yindong (IEEE journal of selected topics in applied earth observations and remote sensing, 2025)
Urban surface heterogeneity leads to significant variability in temperature distribution, complicating the measurement of surface urban heat island intensity (SUHII) and the development of thermal stress mitigation strategies. This study utilizes high spatiotemporal resolution thermal infrared remote sensing data ECOSTRESS and local climate zone (LCZ) classification to analyze SUHII changes at 60 time points in six cities in China with different terrains and elevations in May to September, comparing both inter-LCZ and intra-LCZ differences. The findings indicate that SUHII is strongest at night and weakest at noon, with the peak of spatial heterogeneity occurring around 15:00 and the minimum around 9:00. Cities near 35°N (Xining, Xi'an, and Jinan) exhibit stronger nocturnal heat islands, while high-altitude cities, such as Xigaze (3835 m), demonstrate unique thermal inversions, transitioning from daytime heat sinks to nighttime heat sources. Compact buildings generally experience higher SUHII than open buildings, while vegetation and water bodies act as heat sinks during the day and heat sources at night. Notably, LCZs in high-altitude cities also exhibit inverse thermal behavior. The results enhance the understanding of urban heat island dynamics and emphasize the role of terrain, elevation, and urban structure in managing urban heat and adapting to climate risks.